Family Knowledge about Covid-19 and Family Attitude Towards Family Members Suffering with Covid-19 - Siti Maghfiroh; Triana Arisdiani; Setianingsih Setianingsih (Proceedings of the International Conference on Nursing and Health Sciences, 2021)
Family knowledge about Covid-19 is the beginning of an effort to provide a conducive climate for family members being treated for Covid-19. The family is the most important source of treatment for sick family members and greatly helps increase immunity for family members who are infected with Covid-19. The purpose of knowing family knowledge about Covid-19 and family attitudes towards family members who suffer from Covid-19 at Dr.H. Soewondo Kendal. This study used a descriptive survey study design, a sample of 65 samples, the sampling technique used consecutive sampling. The questionnaire used was family knowledge about Covid-19 and a family attitude questionnaire towards family members who suffered from Covid-19. Statistical analysis using univariate analysis. This research has been declared ethically feasible according to 7 WHO standards with ethically appropriate information number 24/KEPK- RSUD/EC/VII/2021. The results showed that the average age of the respondents was 39 years, the minimum age was 28 years and the maximum age was 58 years, the majority were educated. SMA as much as 55.45%, male 55.4%, working as an employee 26.2%, status in the family of children as much as 43.1%, having good knowledge as much as 49.2%, having a good attitude as much as 75 ,4%. The results of this study are expected to be used as a basis for implementing health promotions to increase family knowledge about Covid-19 so that families are able to determine and make decisions on how to behave towards family members who are infected with Covid- 19.